Complicated diverticular colopathy: Therapeutic attitude - Aizen Tub, Bernardo; Beltrán Guañarita, Jorge; Albo Volonté, Manuel (Cirugía del Uruguay, 1991)
A retrospective analysis is made of 25 patients suffering from acute inflammatory complication of diverticular colopathy. Taking results into account, medica/ management is recommended, reserving surgical treatment for failures and evolutive diffuse peritonitis